Uma tradução premiada sob a perspectiva da lingüística de corpus - Alambert, Eliane Gurjão Silveira (2008)
This study aimed at discover, systematically, features in an awarded translation that could show the translator expertise. Thus, we used the winner of the União Latina in 2006, DNA- O segredo da Vida, translated by Carlos Afonso Malferrari from the originally English written book DNA- The secret of life of James D. Watson. Original and translation were scanned, producing two subcorpora that were aligned in a parallel corpus. The subcorpus containing the translated text was compared with a Portuguese general corpus in terms of vocabulary size, and the results showed that this feature is much alike for both corpora. Based on the fact that a word in English that has a cognate in Portuguese can influence the translation choices, we established two categories, one that presents a direct translation for Portuguese and other that doesn t present a direct translation. A sample with 40 words, 20 of each category, was taken from the parallel corpus to check the translations used for each one. We found that the translator use a number of words in Portuguese for each one in English and that the origin of the word is indifferent to the expert translator, so that it doesn t matter which category the word in English is fit in, for he uses a very similar number of words in Portuguese for each one in English despite its nature. Thus, the results show that the expert translator is committed to the context and is not attached to fixed formulas or predetermined solutions